Exploratory mixed methodology to understand visitor use and perceptions at a National Grassland - Bremser, Katharina (Kansas State University, 2024)
Despite their importance to local communities, National Grasslands are an often overlooked and understudied part of the United States Forest Service. This exploratory study used mixed methodology to better understand visitor perceptions and use regarding National Grasslands by exploring experiences at Cimarron National Grassland. Given the research aim, this study used semi-structured interviews with managers to construct surveys with a combination of quantitative and qualitative data. Then distributed these surveys via social media (n=209). Spectus mobile device data was used to understand visitor spatial use, and semi-structured visitor interviews (n=6) were used to gain richer data on visitor experiences. Principal component analysis identified four components that were used to further analyze visitor perceptions across activity types, showing that the natural environment was rated the highest on a five-point Likert Scales among visitors while conditions of developed facilities was the lowest. These components were used in a multiple linear regression analysis to understand influencers of nature relatedness and quality experiences. It was found that the natural environment positively influences nature relatedness and positively influences visitor quality experience. Visitor use was analyzed using a spatial survey question and mobile device data to identify the most used sites as well as visitor patterns at those sites. Six interviews were conducted with local visitors to gain a better understanding of visitor perceptions of developed facilities. These interviews revealed trail and pond maintenance would be beneficial, and site selection was influenced by activity type, developed facilities, and accessibility. This study is beneficial for CNG managers because it specifies visitor preferences and use, which were not well understood, and demonstrates that visitor survey data collection can successfully be achieved at similar Grassland units.
Keywords: National Grasslands; Visitor use; Mixed methodology; Social media; Cimarron National Grassland